Desain Bagi Hasil usaha berbasis Digital “DEWI KUNTI” (Desa Wisata Akuntabel dan Kreatif) Pada Objek Wisata Kampung Pinus Keditan: Indonesia - safitri, Junaidi; Rakhmawati; Haryono, Kholid; Wahyudi, Rofiul (UII, 2024)
Keditan village has a superior tourist attraction, namely Kampoeng Pinus Keditan which offers a natural panorama in the form of a pine forest and provides interesting spots to visit. Currently, the management of the Kampung Pinus Keditan tourist attraction is carried out simply and conventionally. There are several problems faced by the management of Pinus Keditan Village, namely; 1). There is no agreement regarding the sharing of profits from the Pine Village tourism business between Perhutani, the Village Government and the Landowner Community, 2) The recording of financial reports is still manual, resulting in frequent errors and 3). Lack of skills of Kampoeng Pine managers in promotion, marketing and outbound tourism guides. The aim of this empowerment is the development of Human Resources (HR) governance in the fields of promotion, marketing and outbound tourism guides and the preparation of digital-based financial reports for the results of the Kampoeng Pine Editan business. The method for implementing this service program uses the Participatory Action Research method with 8 main process cycles including 1) Observation, 2) planning, 3) Program development, 4) Socialization 5) Implementation, 6) Reflection, 7) evaluation, and 8) Follow up. The targets for this service are the Keditan village government, Pine Village managers and village communities. The output of this service program is in the form of improving management skills in promotion, marketing and guiding outbound tourism, digital-based profit-sharing applications for Pine Village tourism businesses, village profiles and tourism profiles for Keditan Pine Village.